2005
DOI: 10.1128/aem.71.9.5260-5266.2005
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion of the Entomopathogenic Fungus Beauveria ( Cordyceps ) bassiana to Substrata

Abstract: The entomopathogenic fungus Beauveria bassiana produces at least three distinct single-cell propagules, aerial conidia, vegetative cells termed blastospores, and submerged conidia, which can be isolated from agar plates, from rich broth liquid cultures, and under nutrient limitation conditions in submerged cultures, respectively. Fluorescently labeled fungal cells were used to quantify the kinetics of adhesion of these cell types to surfaces having various hydrophobic or hydrophilic properties. Aerial conidia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
130
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 215 publications
(145 citation statements)
references
References 35 publications
(32 reference statements)
6
130
0
2
Order By: Relevance
“…Conidia of EPF such as M. brunneum and B. bassian a, possess hydrophobins in the outer layer of the cell wall whereas these are absent in blastospores [22]. These differences could influence adhesion and consequently impact on EPF efficacy and probably host specificity [22]. The current study shows for the first time that M. brunneum blastospores have different degrees of adhesion to the cuticles of different insect host species.…”
Section: Discussionmentioning
confidence: 90%
See 4 more Smart Citations
“…Conidia of EPF such as M. brunneum and B. bassian a, possess hydrophobins in the outer layer of the cell wall whereas these are absent in blastospores [22]. These differences could influence adhesion and consequently impact on EPF efficacy and probably host specificity [22]. The current study shows for the first time that M. brunneum blastospores have different degrees of adhesion to the cuticles of different insect host species.…”
Section: Discussionmentioning
confidence: 90%
“…Spore attachment is influenced by hydrophilic and hydrophobic characteristics of the host surface and the fungal cell wall [41]. Holder and Keyhani [22] demonstrated that hydrophilic blastospores of Beauveria bassiana bind rapidly to hydrophilic surfaces and bind poorly to hydrophobic surfaces. However, blastospores require a longer incubation time to bind to weakly polar surfaces than to hydrophilic surfaces.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations